'What's a fixed‐term exclusion, Miss?' Students' perspectives on a disciplinary inclusion room in England. (13th September 2013) - Gilmore, Gwen
<x xml:space="preserve">Abstract</x> Marginalised students in education are often formally excluded and further disadvantaged by school disciplinary approaches. This leads to school behaviour codes not being followed by students. This result is often linked to individualised student disciplinary responses. Further, formal student exclusion from schools remains a controversial international practice driven by eclectic government policy. Yet there is limited research on student perspectives within debates on the value of interventions designed to reduce fixed‐term exclusion and promote children's participation in education. This study, by Gwen Gilmore of the College of Education at Victoria University, Melbourne, presents the perspectives of five Year 8 and 9 students who participated in a disciplinary inclusion room designed to reduce fixed‐term exclusion in a secondary school located in England. The research methodology is framed by a cultural historical activity theory approach, and mixed methods reported include document analysis and student interviews. Students stated that the disciplinary inclusion room enabled them to continue their learning and that this discipline model complemented the processes of education. These students' perspectives challenge recent narratives on disciplinary provision and provide possibilities for schools to consider how discipline can be organised towards practices that are more inclusionary and potentially educative.